The elasticity-based approach to enterprise innovation - Adam Karbowski (International Journal of Management and Economics, 2016)
The goal of this paper is to present a formal model of firm innovation that simultaneously analyzes innovation factors characteristic to the Schumpeterian strand of industrial organization literature and the know-how strand. Corporate R&D intensity serves here as an input measure of firm innovation. R&D intensity can be defined as a ratio of firm's R&D spending to the firm's sales (total revenues). On the basis of formal analysis it is found that R&D intensity is fully determined by three complementary factors, i.e. a firm's technological competence (supply-side factor), consumer preference for quality and price of a product (demand-side factor), as well as a moderator factor associated with the knowledge spillovers, which occur between competing firms in the industry. Since the above factors are expressed in terms of elasticities, the presented model is called an elasticity-based model of firm innovation. Further, within the model framework, it is shown how horizontal R&D cooperation alleviates the free-rider problem that can discourage a firm's innovation activities. It is next postulated that horizontal R&D cooperation can be effectively treated as a complementary tool (to such traditional solutions as patent protection and public research subsidies) for solving the problem of negative externalities in an industry with pervasive knowledge spillovers.
Keywords: L1; L2; O32; 650; research and development; firm innovation; inter-firm cooperation